F53. IMPROVED FUNCTIONAL CAPACITY AND COGNITIVE PERFORMANCE IN CLOZAPINE RESPONDERS COMPARED TO NON-RESPONDERS. (9th April 2019) - Nucifora, Frederick; Baker, Krista; Stricklin, Ashley; Cuerdo, Arlene; Parke, Kathryn; DuBois, Samantha; Nucifora, Leslie; Margolis, Russell; Sawa, Akira; Harvey, Philip
Abstract: Background: Treatment resistant schizophrenia is associated with considerable everyday disability. Disability in schizophrenia is commonly found to be correlated with impairments in cognitive performance and with impairments in performance on measures of functional capacity. What has not been well examined is the association between symptom status, cognitive functioning, and functional capacity in treatment refractory patients and good and poor response to clozapine treatment. In this study, we examine clozapine treated patients and compare the cognitive and functional capacity performance across response status. Methods: Twenty-seven clozapine treated patients were tested with the Brief Assessment of Cognition in Schizophrenia (BACS), were clinically rated with the PANSS, and performed three computerized tests of functional capacity (FC): ATM Banking, Ticket Purchase, and Prescription Refill with a telephone voice menu. Prior to treatment all patients had been designated as treatment refractory and at least moderately ill based on overall clinical state. Patients were divided into groups on the basis of the Andreasen et a. remission criteria as well as being divided on the basis of having moderate or more severe PANSS symptoms (Total>58). Results: Time to completion and efficiency scores for the FC measures were correlated with BACS composite scores in the group as a whole, all Pearson r>.47, all p<.02. Patients who were in remission (n=12) performed faster and more efficiently than those who were not on all FC measures, all t>2.00, all p<.05, all d>.60. Cognitive performance did not differ, t=1.97, p=.061. In comparisons of global symptom severity, patients with mild symptom severity (n=18) performed faster and more efficiently than those who were not on all FC measures, all t>2.07, all p<.05, all d>1.1. Cognitive performance was better in the less symptomatic group, t=3.34, p=.003, d=1.25. Discussion: Positive clozapine treatment response was associated with better performance on measures of both functional capacity and cognitive performance. These differences were significant even in this small sample size and the effect sizes were quite substantial. These data suggest that being a clozapine responder is associated with considerably less impairment in the ability to perform critical functional tasks and in cognitive performance. All patients were severely ill before clozapine treatment and 12 achieved remission. As there are no healthy controls, we cannot make normative statements about performance, but the large effect sizes suggest considerable differences associated with positive clozapine response.